2005
DOI: 10.1113/jphysiol.2005.093740
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐induced electrical activity in rat pancreatic β‐cells: dependence on intracellular chloride concentration

Abstract: A rise in glucose concentration depolarizes the β-cell membrane potential leading to electrical activity and insulin release. It is generally believed that closure of K ATP channels underlies the depolarizing action of glucose, though work from several laboratories has indicated the existence of an additional anionic mechanism. It has been proposed that glucose activates a volume-regulated anion channel, generating an inward current due to Cl -efflux. This mechanism requires that intracellular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 42 publications
(57 reference statements)
8
56
0
1
Order By: Relevance
“…2 mM). These results suggest that insulin secretion may not be reduced in NKCC1 KO mice, as it could be expected from the absence of NKCC1 and the demonstrated dependency that insulin secretion has on [Cl K ] i (Sehlin 1978, Best 2005. Our results do not appear to be related to increased insulin sensitivity of peripheral tissues to insulin (Fig.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…2 mM). These results suggest that insulin secretion may not be reduced in NKCC1 KO mice, as it could be expected from the absence of NKCC1 and the demonstrated dependency that insulin secretion has on [Cl K ] i (Sehlin 1978, Best 2005. Our results do not appear to be related to increased insulin sensitivity of peripheral tissues to insulin (Fig.…”
Section: Discussionsupporting
confidence: 47%
“…WT and NKCC1 KO mice was not (Sehlin 1978, Somers et al 1980, Tamagawa & Henquin 1983, Lindstrom et al 1986, Kinard & Satin 1995, Eberhardson et al 2000, Majid et al 2001, Best 2005, Best et al 2010. We have recently demonstrated that NKCC2 is expressed in b-cells, thus providing a potential additional mechanism for [Cl K ] i regulation in these cells (Alshahrani & Di Fulvio 2012).…”
Section: Homozygous Inactivation Of the Slc12a2 Gene Increases B-cellmentioning
confidence: 92%
See 1 more Smart Citation
“…Chloride ions are transported by an active mechanism in pancreatic β cells (21). Glucose increases chloride efflux in β cells, which could contribute to membrane depolarization (20)(21)(22)(23). Although the identity of the chloride channel(s) in β cells remains unclear, it has been proposed that certain unidentified chloride channels expressed in the plasma membrane might be involved in the regulation of electrical activity and insulin secretion in β cells (24,25).…”
Section: Ins-ano1mentioning
confidence: 99%
“…S1). ANO1 is a calcium-activated chloride channel protein (17)(18)(19); chloride ion levels in β cells are known to influence insulin secretion (20)(21)(22)(23), and it has been proposed that one or more chloride channels contribute to the regulation of plasma membrane electrical activity and insulin secretion in β cells (24,25). ANO1 protein and its closest homolog ANO2 are expressed mainly in the plasma membrane and act as membrane calcium-activated chloride channels (17)(18)(19), but whether other members of the ANO family are also plasma membrane chloride channels in vivo remains unclear (26,27).…”
Section: Ins-ano1mentioning
confidence: 99%